Analisis Peran Daya Tahan Kardiorespirasi (VO₂Max) terhadap Performa Atlet Sepakbola: Tinjauan Pustaka Sistematis - Fariel Krisyaul Putra; Bambang Priyono (MAN Insan Cendekia Jambi, 2026)
This study aims to examine the role of cardiorespiratory endurance (VO₂Max) in soccer player performance. This study used the Systematic Literature Review (SLR) method to analyze the role of cardiorespiratory endurance (VO₂Max) in soccer player performance, following the PRISMA guidelines in the article selection and analysis process. The keywords performance, soccer, and VO₂Max were used to search for relevant articles published between 2021 and 2025 in the Scopus database. A literature search in the database identified 168 articles. From 2021 to 2025, categorical articles (n=76) and inaccessible articles that did not meet the inclusion criteria (88) were selected from the entire database. Furthermore, filtered articles were selected based on keywords related to performance, Soccer, VO₂Max (n=42), and then relevant articles (n=10) were selected. Conclusion, VO₂Max plays an important role in improving heart and lung endurance, maintaining concentration, and supporting players' repeated sprint ability. Good aerobic capacity helps speed up the energy recovery process so that players can maintain game intensity and reduce fatigue. Improvements in VO₂Max can be achieved through systematic training programs such as interval and circuit training. Proper training planning by coaches according to the needs and characteristics of athletes can achieve optimal performance.